Smart grid : communication-enabled intelligence for the electric power grid - Bush, Stephen F.; Books24x7, Inc. (Chichester, West Sussex, U.K. : John Wiley & Sons Ltd., 2014)
"This book bridges the divide between the fields of power systems engineering and computer communication through the new field of power system information theory. Written by an expert with vast experience in the field, this book explores the smart grid from generation to consumption, both as it is planned today and how it will evolve tomorrow. The book focuses upon what differentiates the smart grid from the "traditional" power grid as it has been known for the last century. Furthermore, the author provides the reader with a fundamental understanding of both power systems and communication networking. It shows the complexity and operational requirements of the evolving power grid, the so-called "smart grid," to the communication networking engineer; and similarly, it shows the complexity and operational requirements for communications to the power systems engineer. Each part is divided into chapters and each chapter has a set of questions useful for exercising the readers' understanding of the material in that chapter. --
Title from title screen.
Includes bibliographical references and index.
Text.
Available also in a print ed.
Mode of access: Internet via World Wide Web.
Digitized and made available by: Books24x7.com.
Keywords: Smart power grids; Electronic books; Electronic books